Subclinical Atherosclerosis among HIV-Infected Adults Attending HIV/AIDS Care at Two Large Ambulatory HIV Clinics in Uganda - Ssinabulya, Isaac; Kayima, James; Chris, Longenecker; Luwedde, Mary; Semitala, Fred; Kambugu, Andrew; Ameda, Faith; Bugeza, Sam; Grace, McComsey; Juergen, Freers; Nakanjako, Damalie (PLOS One, 2014)
Background The increased immune activation and inflammation of chronic HIV-infection and the characteristic dyslipidemias associated with HIV infection and antiretroviral therapy (ART) contribute to an increased risk of atherosclerotic vascular disease among HIV-infected adults. There is an emerging need to understand determinants of cardiovascular disease (CVD) among individuals aging with HIV in sub-Saharan Africa. We determined the prevalence of subclinical atherosclerosis [carotid intima media thickness (CIMT) ≥0.78 mm] and its correlation with traditional CVD risk factors among HIV-infected adults. Methods In a cross-sectional study, HIV-infected adults (ART-naïve and ART-treated) were consecutively selected from patients' enrollment registers at two large HIV clinics at Mulago Hospital, Kampala, Uganda. We measured traditional CVD risk factors including age, biophysical profile, fasting blood sugar and serum lipid profile as well as biomarkers of inflammation. High resolution ultrasound was used to measure common carotid CIMT. Results Of 245 patients, Median age [Interquartile range (IQR)] 37 years (31–43), 168 (69%) were females; and 100 (41%) were ART-treated for at least 7 years. Overall, 34/186 (18%) had subclinical atherosclerosis; of whom 15/108 (14%) were ART-naïve whereas 19/78 (24%) were ART-treated. Independent predictors of subclinical atherosclerosis included age [odds ratio (OR) 1.83 per 5-year increase in age; 95% confidence interval (CI) 1.24–2.69; p = 0.002], body mass index (BMI); OR 1.15; CI 1.01–1.31; p = 0.041 and high low density lipoprotein (LDL) [OR 2.99; CI 1.02–8.78, p = 0.046]. High sensitivity C-reactive protein (hsCRP) was positively correlated with traditional cardio-metabolic risk factors including waist circumference (r = 0.127, p = 0.05), triglycerides (r = 0.19, p = 0.003) and Total Cholesterol: High Density Lipoprotein ratio (TC:LDL) (r = 0.225, p<0.001). Conclusion The prevalence of subclinical atherosclerosis was 18% among HIV-infected adults in Uganda. Traditional CVD risk factors were associated with subclinical atherosclerosis. We recommend routine assessment of traditional CVD risk factors within HIV care and treatment programs in sub-Saharan Africa.